2002
DOI: 10.1002/gepi.0164
|View full text |Cite
|
Sign up to set email alerts
|

Mortality differences by APOE genotype estimated from demographic synthesis

Abstract: The 4 allele of apolipoprotein E (APOE) is associated with increased risk of two major causes of death in low-mortality populations: ischemic heart disease and Alzheimer's disease. It is less common among centenarians than at younger ages. Therefore, it is likely that it is associated with excess risk of death. This article extends demographic models that estimate relative mortality risks from changes in gene frequencies with age. The resulting demographic synthesis combines gene frequencies with data on morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
78
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 29 publications
(34 reference statements)
7
78
4
Order By: Relevance
“…First, the number of participants which analyzed in the previous centenarian studies were small (N = 33, 103, and 179, respectively, Asada et al 1996;Choi et al 2003;Sobel et al 1995). Second, the APOE gene has been associated with longevity; centenarians tend not to have the APOE ε4 allele (Ewbank 2002;Farrer et al 1997). The selective survival effect for APOE ε4-negative individuals makes it difficult to evaluate the effect of APOE on outcomes in very late life population.…”
Section: Discussionmentioning
confidence: 99%
“…First, the number of participants which analyzed in the previous centenarian studies were small (N = 33, 103, and 179, respectively, Asada et al 1996;Choi et al 2003;Sobel et al 1995). Second, the APOE gene has been associated with longevity; centenarians tend not to have the APOE ε4 allele (Ewbank 2002;Farrer et al 1997). The selective survival effect for APOE ε4-negative individuals makes it difficult to evaluate the effect of APOE on outcomes in very late life population.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table I, heterogeneity has a profound effect on the power of a non-parametric approach. Several authors have tried to estimate the parameters using a gamma frailty model Tan et al, 2001a;Ewbank, 2002] in fitting survival functions to individual genotype data but found that the estimated variance of the unobserved frailty varies considerably in different studies, perhaps due to small sample sizes used. Based on our experience in fitting survival distributions to large population data, we set s 2 to 0.1 in our simulation to ensure a reliable result.…”
Section: Discussionmentioning
confidence: 99%
“…Another significance of heterogeneity is relevant to association studies. Given the existence of competing risk factors or heterogeneity, the risk for any particularly observed factor (including genetic factors) will tend to decline [Ewbank, 2002]. In our simulation, we set the risk of the allele constant at the individual level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations